Pediatric and adolescent injury in mountain biking - Caine, D. J.; Young, K.; Provance, A. J. (Research in Sports Medicine, 2018)
Mountain-biking has become a popular competitive and recreational activity but also involves risk of injury. This article provides an overview of what is known about the scope of the injury problem affecting children and adolescent mountain bikers, the risk factors involved and injury prevention strategies. The proportion of injured child and adolescent mountain bikers ranges from 10.6% to 64.0%, but few studies provide separate analysis of youth injuries. Upper extremity injuries appear most common except among adolescents where the risk of head injury and traumatic brain injuries are greater. Concern is raised regarding the reported frequency of spine fractures and spinal cord injuries. Multi-faceted, longitudinal injury research focusing on youth mountain bikers is required to provide a reliable basis for testing risk factors and evaluating preventive measures. Reducing mountain biking-related injuries will require multiple strategies that integrate approaches from education, engineering, and evidence-based safety measures and their enforcement.